In vitro safety evaluation of Bacillus subtilis species complex isolated from Vietnam and their additional beneficial properties - Thi Lan Anh, Hoang; Thi Thanh Hue, Le; Hai Linh, Bui Nguyen; Tuan Dung, Nguyen Huu; Duong Minh, Dao; Thi Le Quyen, Tran; Trung, Trinh Thanh (Vietnam Journal of Biotechnology, 2022)
Bacillus genus are Gram-positive, rod shaped, spore-forming, aerobic or facultative anaerobic bacteria, which have the ability to produce a wide variety of enzymes, antimicrobial compounds, vitamins, and carotenoids. Nowadays, Bacillus species have been increasingly proposed for use as probiotics or feed additives as B. amyloliquefaciens, B. licheniformis, B. subtilis, and B. pumilus because of their advantages such as heat-stability of the spores, storage capacity at ambient temperature, and beneficial properties for health. Since microbes are used for customers and livestock, it is critical to substantiate not only the health benefits and efficacy of unique strains but also their safety for the hosts. This study aims to evaluate the in vitro safety and some beneficial properties of Bacillus strains to select potential strains for use in humans or animals. A total of 76 Bacillus strains belonged to the B. amyloliquefaciens and B. subtilis groups were preliminary evaluated for their safety via hemolytic activity. Six non-hemolytic strains were identified and their antibiotic susceptibility, cytotoxicity on the growth of HT29 and Vero cells, extracellular enzyme production, antimicrobial activity, and identification based on 16S rRNA and rpoB gene sequences were studied. Two strains, B. subtilis VTCC 10963 and B. subtilis VTCC 11039, should be considered safe. In addition, these two strains exhibited good extracellular enzyme production (amylase, cellulase, and protease) and strong antibacterial activity against Listeria monocytogenes. Our results support the use of B. subtilis VTCC 10963 and B. subtilis VTCC 11039 for the development of probiotic products and feed additives in the future.